Sudoku Solver - Mohammad Masood; Yacoob Assi (My University, 2023)
This project showcases a Sudoku solver that combines image processing and robotic manipulation to automate the process of solving Sudoku puzzles. By utilizing a camera connected to a Raspberry Pi, the system captures an image of a Sudoku board, extracts the numbers and their positions from the image, and employs an algorithm to solve the puzzle. A robotic arm equipped with a pen attachment then fills in the solved numbers on the physical board. This integration of image processing, robotics, and algorithmic solving demonstrates the potential of combining technologies to automate complex puzzle-solving tasks. 4